ANALISIS KOMPARATIF EKSTRAK BEBERAPA JENIS RIMPANG TERHADAP PATOGEN PENYEBAB BUSUK BUAH KAKAO (Phytophthora palmivora Butler.): Comparative Analysis of Extracts from Several Types of Rhizomes Against the Pathogen Causing Cocoa Fruit Rot (Phytophthora palmivora Butler) - Nur, Nur Hidayat Burhanuddin; Sayang, Yulis `; Sugiarti, Ade (Journal Agroecotech Indonesia (JAI), 2025)
This study aimed to determine the effect of using several types of rhizome extracts in controlling the fungus Phytophthora palmivora Butler, the causative agent of cacao fruit rot, and to analyze the comparative effects of these extracts in controlling P. palmivora Butler. The research was conducted in the Plant Protection Laboratory, Faculty of Agriculture, Universitas Islam Makassar, from February to April 2025. Symptomatic fruit peel samples measuring approximately 1 cm² were collected (5 samples). The symptomatic fruit peels were then isolated and identified. After purification, botanical pesticides were applied using Potato Dextrose Agar (PDA). The research method used was a Completely Randomized Design (CRD) with five rhizome extract treatments and one control, each replicated four times. The extract concentration used was 2.5%. Data analysis was performed using ANOVA and the BNT test at a 5% significance level. The results showed that all rhizome extracts significantly inhibited the growth of P. palmivora Butler. Red ginger extract showed the highest inhibitory power (100%), followed by fingerroot (93.06%), turmeric (72.74%), temulawak (72.27%), and galangal (60.69%). Red ginger extract is the primary choice, while fingerroot extract can be an effective and environmentally friendly alternative for controlling cacao fruit rot.